Using relative importance index method for developing risk map in oil and gas construction projects - Mukhtar A. Kassem,; Muhamad Azry Khoiry,; Noraini Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this research is to classify risk factors and their ranking in terms of their probability and impact on construction projects in the oil and gas sector, to test the relationship between the causes and effects of risk factors and then develop the risk map to facilitate the planning of risk response strategies. To achieve this objective, researchers invited practitioners and engineers who are comprising a statistically representative sample of oil and gas sector population to joining a structured questionnaire survey. A total of fifty-one (51) factors were short-listed to be made part of the questionnaire survey. The survey was conducted with 357 participants of construction project teams as a sampling of populations from all oil and gas sectors in Yemen. The relative importance index (RII) method was applied to prioritize the project risk factors. RII data were used to develop a risk map for oil and gas construction projects. Correlation coefficient and reliability tests also carried out to know the relationship between risk factors and check the validity of the research. The reliability test of the questionnaire was 0.974 for the cause of risks and 0.81 for the effects, which considered very high value. RII analysis and risk map shown the most critical risk factors effected on project success. There is a significant contribution expected from this research, especially for companies operating in the oil and gas and other organizations that plan to invest in this field, in addition to expected benefits for the governments and researchers in this field due to lack of research in this field.